An Observational Study on the Humoral and Cellular Immune Response to SARS-CoV-2 mRNA Vaccination in Multiple Sclerosis and Other Autoimmune Neurological Disorders Treated With Anti-CD20 Therapies. (5th December 2022) - Borko, Tyler L.; Selva, Sean; Baxter, Ryan; Cabrera-Martinez, Berenice; Rester, Cody; Sillau, Stefan; Pastula, Daniel M.; Sabalza, Maite; Venkataraman, Iswariya; Thiruppathi, Eagappanath; Bennett, Jeffrey L.; Alvarez, Enrique; et al.
Abstract : Objective: To assess adaptive immunity to SARS-CoV-2 in anti-CD20 treated individuals with mRNA vaccination. Background: Anti-CD20 therapies attenuate humoral responses to vaccines. However, their effect on T cell responses is less clear. We examined B and T cell responses following COVID-19 vaccination in patients receiving anti-CD20 therapy for multiple sclerosis (MS) and other autoimmune inflammatory neurologic diseases (AINDs, e.g., autoimmune encephalitis, stiff person syndrome, etc.). Design/Methods: MS and AIND patients on anti-CD20 therapies were prospectively enrolled for longitudinal analysis of antibody and T cell responses after a 3rd COVID-19 vaccination. Serum antibodies against the receptor-binding domain of the S1 spike protein (RBD-S1 IgG), neutralizing antibodies, and SARS-CoV-2 CD8 T cell responses, using activation-induced markers (AIM) and INF-γ release assays (EUROIMMUN, Germany), were measured at various time points including pre-vaccination, post initial vaccination series, and 4 and 12 weeks after 3rd dose. Results: Thirty-four MS and AIND participants are enrolled. Results for these patients (mean age 52 years-old, 79% female, 21 Pfizer, 13 Moderna) demonstrated attenuated RBD IgG antibody responses. However, a robust CD8 T cell response was observed, following a two-dose series, compared to non-immunosuppressed, age-matched vaccinated controls or unvaccinated with severe SARS-CoV-2 infection (p = 0.01). T cell response was sustained long-term (>12 weeks post 3rd dose) in all 11 anti-CD20 patients analyzed thus far. Collections are completed for all participants at 12 weeks and analysis to be completed by 05/15/22. Further analysis includes correlation of the INF- γ release assay compared to RBD-CD8 T cell response detected by AIM assay. Conclusions: Results suggest that patients treated with anti-CD20 therapy generate a robust CD8 T cell response to SARS-CoV-2 mRNA after three doses but remain with attenuated humoral immune responses. Our observational study will provide important data to guide vaccine management in patients on or anticipating anti-CD20 therapy.